-2/3x(-9x+24)=2x-4

Simple and best practice solution for -2/3x(-9x+24)=2x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/3x(-9x+24)=2x-4 equation:



-2/3x(-9x+24)=2x-4
We move all terms to the left:
-2/3x(-9x+24)-(2x-4)=0
Domain of the equation: 3x(-9x+24)!=0
x∈R
We get rid of parentheses
-2/3x(-9x+24)-2x+4=0
We multiply all the terms by the denominator
-2x*3x(-9x+24)+4*3x(-9x+24)-2=0
Wy multiply elements
-6x^2(-+12x(--2=0
We use the square of the difference formula
-6x^2(-12x(+2=0

See similar equations:

| 2n2-5n-7=0 | | -50=-5n-10 | | x+3=-x+21 | | 1096+0.6x=96+0.11x | | x-0.2x=336 | | 2(3n+1)=26 | | 1,128=6(x+17) | | 1725m÷2=862.1 | | 5+4w=35 | | 2s=685+85 | | 27=6-x-4x | | x²+4x+15=0 | | -7x+6(3x-7)=-26-5x | | 15x^2+10=35x | | 85*x=560 | | 66+40+2y= | | 6x-48=4x-10+180 | | (2/x)+3=(2/3x)+(28/9) | | 3.5(x=6)=63 | | X+2/3+x+3=11/6 | | 20x=36+16x | | X+8=14-2x | | 13=(8x-6)+2x | | 5p=2.5 | | 33=5(b)^8 | | 5(2x-3)-6x=3(3x+5) | | 9(j−88)=45 | | (8-z)(2z-1)=0 | | 19.07-19.6k=-11.3k-16.43-10.8k | | 23x+14x=-12 | | 9(j-88)=44 | | 46=46.4.9x^2 |

Equations solver categories